1982
DOI: 10.1093/carcin/3.9.1045
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis of nitrosation in vitro and in vivo in rats by catechin and resorcinol and inhibition by chlorogenic acid

Abstract: Measurements were made of the effects of phenolic compounds, some of which are present in the human diet, on the nitrosation of proline by nitrite to give N-nitrosoproline (NPRO). In vitro, resorcinol, catechin, p-nitrosophenol and phenol were catalysts and chlorogenic acid an inhibitor; guaiacol showed a marginal catalytic effect. Both the catalytic and the inhibiting effects were dependent on pH and on the concentration of phenolic compounds; catalysis by resorcinol and catechin was increased at optimal rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Nitrosation of Morpholine in Rat ---We performed and improved this method according to methods used by Pignatelli et al 27) Six-week-old Wistar male rats (Japan SLC, Hamamatsu, Japan) were housed in an air-conditioned room and given CE-2 commercial food pellets (Crea Japan, Tokyo, Japan) ad libitum. Five rats were assigned to each experimental group.…”
Section: Determination Of Catechin Concentration Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrosation of Morpholine in Rat ---We performed and improved this method according to methods used by Pignatelli et al 27) Six-week-old Wistar male rats (Japan SLC, Hamamatsu, Japan) were housed in an air-conditioned room and given CE-2 commercial food pellets (Crea Japan, Tokyo, Japan) ad libitum. Five rats were assigned to each experimental group.…”
Section: Determination Of Catechin Concentration Inmentioning
confidence: 99%
“…Pignatelli et al reported the catalytic action of catechins and resorcinol on the nitrosation of proline in vitro. 27) A conceivable mechanism has been thought for the catalysis of nitrosation by some of phenolic compounds. C-nitroso derivatives may be formed by further reaction with the nitrosating species to generate a more powerful nitrosating agent, which could be a nitrosoquinone oxime derivative.…”
Section: Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…In early studies catechins were investigated as potential carcinogens; Pignatelli [34] reported in 1982 the increased nitrosation of proline to the carcinogenic N-nitrosoproline, but soon antioxidant properties of catechins, interpreted as chemopreventive effects, became apparent. The first case control study of green tea extracts and cancer incidence was published in 1984 [35].…”
Section: Current Concepts Of Chemopreventionmentioning
confidence: 99%
“…Chlorogenic acid also has been reported to block in vitro and in vivo nitrosation of proline by nitrite (123) and to inhibit the in vitro formation of nitrosamines from amine and nitrite (724). In addition to blocking the ultimate carcinogenic metabolites of polycyclic aromatic hydrocarbons which attack cellular DNA, caffeic acid, ferulic acid and chlorogenic acid have been shown to inhibit the mutagenicity and to accelerate the disappearance from aqueous solution of bay-region diol epoxides of polycyclic aromatic hydrocarbons which are the ultimate carcinogenic metabolites of polycyclic aromatic hydrocarbons (56).…”
Section: Phenolic Compounds In Food and Cancer Prevention 19mentioning
confidence: 99%